IMPLEMENTING FOREST TENURE REFORMS: PERSPECTIVES FROM INDONESIA’S FORESTRY AGENCIES - Tuti Herawati; Esther Mwangi; Nining Liswanti (Indonesian Journal of Forestry Research, 2019)
Forest Tenure Reform implementation involves diverse actors with multiple roles and interests, including government officials. Few studies have attempted to systematically document the conditions facing government agency implementers in their efforts to implement forest tenure reform. This study attempts to identifies factors that enhance or constrain reform implementation from the perspective of individual implementers at national and sub-national levels in Indonesia. The study was conducted through analysing data that resulted from bureaucrat’s interview who purposively selected at Central and Local Government. Most interviewees indicate that forest tenure reforms have three interrelated objectives: to conserve forests and restore degraded forests, to improve community livelihoods and ensure benefits are equitably distributed; and to secure the rights of local, forest-adjacent or forest-dwelling communities. Reform implementation has been effective or somewhat effective in protecting community rights to access, use, manage and benefit from forests. Close to half of the respondents indicated that their activities gave special consideration to low income groups but few paid special attentions to women and women’s rights.  Main constraints to implementation are inadequate budgets and insufficient manpower to execute tenure-related activities. Divergent priorities between national and sub-national/local levels and changes in government that redistribute personnel are additional factors that hinder reform implementation. Overall, respondents agree that reforms are only partially implemented due to technical and institutions constraints, which in turn influence the extent to which collaboration/coordination among actors can be achieved and the extent to which community tenure needs such as conflict management and resolution can be addressed.